5‐Substituted (1‐Thiolan‐2‐yl)cytosines as Inhibitors of A. aeolicus and E. coli IspE Kinases: Very Different Affinities to Similar Substrate‐Binding Sites. Issue 5 (3rd January 2013) - Schütz, Andri P.; Locher, Sebastian; Bernet, Bruno; Illarionov, Boris; Fischer, Markus; Bacher, Adelbert; Diederich, François
Abstract: The enzymes of the non‐mevalonate pathway for isoprenoid biosynthesis are potential new targets for the development of selective drugs for the treatment of important infectious diseases. This pathway is used by major human pathogens, such as Plasmodium falciparum and Mycobacterium tuberculosis, but not by humans. The fourth enzyme in the pathway is the kinase IspE, and we report here the development and biological evaluation of new ligands for this enzyme from Escherichia coli and Aquifex aeolicus species as model systems for the pathogenic enzymes. The study focuses on analysis of the methylerythritol pocket of the 4‐diphosphocytidyl‐2‐ C ‐methyl‐D ‐erythritol binding site. A series of 5‐substituted 1‐(thiolan‐2‐yl)cytosines with increasingly polar substituents were synthesized, opting for possible water‐replacements in that sub‐pocket as well as a high water‐solubility of the ligands. In vitro studies showed IC 50 values in the micromolar range against E. coli IspE, but, unexpectedly, no inhibition against A. aeolicus IspE within the measurement range of the biological tests. Abstract : We report the design, synthesis, and biological evaluation of N(1)‐thiolan‐2‐ylated and C(5)‐substituted ligands. The compounds were used to explore the molecular recognition properties of the methylerithritol sub‐pocket of the substrate binding site in IspE proteins from Escherichia coli and Aquifex aeolicus, which are model enzymes for Plasmodium falciparum IspE, the causative agent of malaria.